The Role of Apelin/Apelin Receptor in Energy Metabolism and Water Homeostasis: A Comprehensive Narrative Review - Hu, Gonghui; Wang, Zhen; Zhang, Rumin; Sun, Wenping; Chen, Xiaoyu (Frontiers in Physiology, 2021)
The apelin receptor (APJ) is a member of the family A of G-protein-coupled receptors (GPCRs) and is involved in range of physiological and pathological functions, including fluid homeostasis, anxiety, and depression, as well as cardiovascular and metabolic disorders. APJ was classically described as a monomeric transmembrane receptor that forms a ternary complex together with its ligand and associated G proteins. More recently, increasing evidence indicates that APJ may interact with other GPCRs to form heterodimers, which may selectively modulate distinct intracellular signal transduction pathways. Besides, the apelin/APJ system plays important roles in the physiology and pathophysiology of several organs, including regulation of blood pressure, cardiac contractility, angiogenesis, metabolic balance, and cell proliferation, apoptosis, or inflammation. Additionally, the apelin/APJ system is widely expressed in the central nervous system, especially in neurons and oligodendrocytes. This article reviews the role of apelin/APJ in energy metabolism and water homeostasis. Compared with the traditional diuretics, apelin exerts a positive inotropic effect on the heart, while increases water excretion. Therefore, drugs targeting apelin/APJ system undoubtedly provide more therapeutic options for patients with congestive heart failure accompanied with hyponatremia. To provide more precise guidance for the development of clinical drugs, further in-depth studies are warranted on the metabolism and signaling pathways associated with apelin/APJ system.